(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
The purpose of this study is to assess the subjective responses on uncomfortable sensation, usability, overall satisfactory level and preference while wearing five types of personal protective equipment (PPE) ensembles. Ten subjects exercised on a treadmill, worked on a computer, and moved a mannequin in a simulated environment, replicating a health care worker